Achieving strength-ductility synergy in metallic glasses via electric current-enhanced structural fluctuations - Ding, Huaping; Gong, Pan; Chen, Wen; Peng, Zhen; Bu, Hengtong; Zhang, Mao; Tang, Xuefeng; Jin, Junsong; Deng, Lei; Xie, Guoqiang; Wang, Xinyun; Yao, Ke-fu; et al. (International journal of plasticity, 2023)
•Electric currents endow Zr-based metallic glasses with an exceptional combination of ultra-high strength, considerable plasticity, and enhanced strain-hardening ability.•Electric currents construct a unique structural fluctuation featuring soft zones surrounded by hard zones.•Plausible mechanisms for such electric current-regulated plasticity in metallic glasses are proposed. Structural applications of metallic glasses are limited by their room-temperature brittleness and strain-softening, associated with the extreme localization of plastic flow in shear bands. Herein, we alleviate this dilemma by the structural fluctuation induced by electric currents, achieving simultaneous improvement of strengths, compression plasticity, and strain hardening capacity. The electric current enhances the structural fluctuations at the atomic scale, introducing more soft zones while densifying their surroundings, which differs from previously reported rejuvenation strategies. This unique structural pattern featuring soft zones surrounded by hard zones leads to extensive sprouts and interactions of shear bands, capturing substantial atoms to participate in the deformation. The plausible mechanism behind the electric current-influenced dynamic evolution of amorphous clusters is proposed. Electric current introduces interatomic electrostatic forces between shell atoms of amorphous clusters through charge transfer. This force decreases the coordination of Zr- and Cu-centered clusters and increases the Al-centered icosahedra in the glassy matrix. Differential evolution of clusters under electric currents enhances atomic structural fluctuations and originates from the cohesion mechanism determined by electron distribution. These findings are suggestive of vanishing room-temperature brittleness and shed atomic-scale light on modulations of the structure and properties of metallic glasses by electric currents. [Display omitted]